Parental satisfaction with paediatric care, triage and waiting times. (April 2014) - Fitzpatrick, Nicholas; Breen, Daniel T; Taylor, James; Paul, Eldho; Grosvenor, Robert; Heggie, Katrina; Mahar, Patrick D
Abstract Objective The present study aims to determine parental and guardian's perceptions of paediatric emergency care and satisfaction with care, waiting times and triage category in a community ED. Methods A structured questionnaire was provided to parents or guardians of paediatric patients presenting to emergency. The survey evaluated parent perceptions of waiting time, environment/facilities, professionalism and communication skills of staff and overall satisfaction of care. Results One hundred and thirty‐three completed questionnaires were received from parents of paediatric patients. Responses were overall positive with respect to the multiple domains assessed. Parents generally considered waiting times to be appropriate and consistent with triage categories. Overall satisfaction was not significantly different for varying treatment or waiting times. Patients triaged as semi‐urgent were of the opinion that waiting times were less appropriate than urgent, less‐urgent or non‐urgent patients. Conclusion On the basis of the present study, patient perceptions and overall satisfaction of care does not appear to be primarily influenced by time spent waiting or receiving treatment. Attempts made at the triage process to ensure that semi‐urgent patients have reasonable expectations of waiting times might provide an opportunity to improve these patients' expectations and perceptions.